Evaluation of Trainees’ Post-Training Competency in the South African Police Service - Moitsadi, Zitha; Aphane, Mmabatho P.; Mofokeng, Lerato; Mofokeng, Jacob T. (Publica: Jurnal Pemikiran Administrasi Negara, 2024)
This paper presents the findings on the respondents’ perceptions of trainees’ competency after completing training. A survey was conducted among 329 respondents from 13 police stations in the Johannesburg policing area using a questionnaire. The findings revealed that contextual factors, namely effectiveness, training environment and trainer’s skills as well as adequate resources towards development have a positive impact on the programme conducted at the training centres. Furthermore, the findings highlighted that the respondents were of the view that, since the inception of new methods of training after the 1994 democratic elections, the South African Police Service (SAPS) had demonstrated a progressive development towards responding to community matters. However, there were gaps in the training and development programmes such as lack of resources, the blanket approach to training and the training models focusing on current challenges rather than future trends. To address these challenges within the SAPS and ensure that there is effective training and development for organisational performance, there is a need to ensure that there are adequate resources for training and development. The training and development procedures within the SAPS also need to adopt international standards. The management at the Johannesburg Training Centre also needs to come up with an effective strategy to identify the needs and skills gaps of employees and ensure that these are addressed in an ever-changing and improving training and development strategy. This study provides critical input and makes a contribution to the literature related to training in the SAPS in South Africa.